Free-polymer controlling morphology of α-MoO3nanobelts by a facile hydrothermal synthesis, their electrochemistry for hydrogen evolution reactions and optical properties - Hathai Sinaim (2018)
Orthorhombic molybdenum oxide (α-MoO3) nanobelts were successfully synthesized by the 100-180 °C and 2-20 h hydrothermal reactions of (NH4)6Mo7O24·4H2O solutions containing 15 ml 2 M acid (HNO3, H2SO4or HCl) with no surfactant and template adding. These products were characterized by X-ray diffraction (XRD), Fourier transform infrared (FTIR) and Raman spectroscopy, and electron microscopy (EM). In the present research, the product synthesized by the 180 °C and 20 h hydrothermal reaction of the solution containing HNO3was α-MoO3nanobelts with >10 μm long and <200 nm wide. Electrochemistry for hydrogen evolution reactions (HER) and optical properties of the as-synthesized α-MoO3nanobelts were characterized by linear sweep voltammetry (LSV) and Tafel plot, including UV-vis and photoluminescence (PL) spectroscopy. These imply that α-MoO3nanobelts show satisfied performance for HER, with the 3.75 eV direct allowed band gap (Eg) due to the charged transition of O2p→ Mo4d, including the emission of 437 nm wavelength at room temperature. © 2011 Elsevier B.V. All rights reserved.